The Role of Antiplatelet Therapy in Patients With MINOCA - Ortega-Paz, Luis; Galli, Mattia; Capodanno, Davide; Brugaletta, Salvatore; Angiolillo, Dominick J. (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous group of clinical entities characterized by the common clinical evidence of myocardial infarction (MI) with non-obstructive coronary arteries on coronary angiography and without an overt cause for the MI. Platelets play a cornerstone role in the pathophysiology of MI with obstructive coronary arteries. Accordingly, antiplatelet therapy is recommended for treating patients with MI and obstructive coronary disease. However, the role of platelets in the pathophysiology of MINOCA patients is not fully defined, questioning the role of antiplatelet therapy in this setting. In this review, we will assess the role of antiplatelet therapy in MINOCA with a focus on the pathophysiology, therapeutic targets, current evidence, and future directions according to its different etiologies.